Culturally mixed groups on international campuses: an opportunity for inter-cultural learning - Volet, S.; Ang, Grace (Routledge, 2012)
One of the major educational goals of the internationalisation of higher education is to prepare students to function in an international and inter-cultural context. Cultural diversity on university campuses creates ideal social forums for inter-cultural learning, yet, one of the most disturbing aspects of the internationalisation of higher education in Australia is the lack of interactions between local and international students from Asian backgrounds. This article examines the factors which students believe are affecting the formation of mixed groups for the completion of academic tasks. It also explores the nature of change in students' perceptions after a successful experience of mixed group work. The focus on both local and international students' appraisals of the situation highlights the two-way, interactive nature of group formation and shows how both parties share some responsibility in the lack of cultural mix.